IMPLEMENTATION OF THE SMART METHOD IN THE DECISION SUPPORT SYSTEM FOR PENALTY RECOMMENDATIONS - Novita Br Ginting; Dahlia Widhyaestoeti; Jejen Jaenuddin; Fitria Rachmawati; Yusup Maolani (LPPM Nusa Mandiri, 2023)
Sanctions need to be given to students who do not obey school rules, and the purpose is to establish student discipline and ethics. SMK Gazza Wiguna 1 Megamendung Bogor district also imposes sanctions for students who violate the rules of conduct. The problem is that determining the violation point has not been done objectively. To overcome this, applying the Simple Multi-Attribute Rating Technique Method (SMART) method to the decision support system to determine recommendations for sanctions for students who commit violations. This system is designed to use UML tools and is built on a web basis. The system uses an alternative oral warning, first warning letter, second warning letter, third warning letter, and returned to parents (DO). The criteria include violation of school uniforms, tidiness, discipline, cleanliness, order, hospitality, commemorating national holidays, and additional provisions. The type of criteria used is the cost criteria because it is expected that students do not violate school rules; if students commit violations, it is hoped that students do not commit serious transgressions.